Scale-resolving investigation of submarine geometry and maneuvering effects on vortex structures - Yılmaz, Naz (American Institute of Physics, 2026)
This study presents a comprehensive numerical investigation of the unsteady flow dynamics around submarine geometries using scale-resolving simulation techniques integrated with an adaptive mesh-refinement strategy. Initially, a baseline submarine model was analyzed using the Reynolds-averaged Navier–Stokes approach, and the numerical results were validated against experimental data from the open literature to ensure accurate prediction of hydrodynamic resistance. Subsequently, several alternative sail configurations were developed and subjected to computational analysis to reduce the overall resistance. These configurations were evaluated not only in terms of total resistance but also through detailed examination of local flow phenomena and vortex structures in the vicinity of the sail. In the next stage, high-fidelity simulations were conducted using a detached eddy simulation framework coupled with adaptive mesh refinement to capture the complex, unsteady flow features with greater resolution. This phase of the study also included the analysis of the submarine's hydrodynamic performance under various maneuvering scenarios, with an emphasis on the evolution and interaction of vortical structures near the appendages. Furthermore, comparative assessments were carried out for both the original and modified sail designs under straight-line motion as well as in pitch and yaw maneuvers. The findings revealed that the modified sail configuration, incorporating a streamlined tail extension, exhibited reduced resistance characteristics relative to the baseline model. Additionally, a marked suppression of horseshoe vortex formation around the sail was observed, along with distinct variations in vortex behavior across different maneuvering conditions. © 2026 Author(s).
Keywords: Hydrodynamics; Mesh generation; Navier Stokes equations; Reynolds equation; Structure (composition); Submarines; Unsteady flow; Accurate prediction; Adaptive mesh refinement; Flow dynamics; Numerical investigations; Numerical results; Refinement strategy; Reynolds-averaged-navier-stokes approaches; Simulation technique; Submarine model; Vortex structures; Vortex flow